Physiological comparison of concentric and eccentric arm cycling in males and females - Beaven, C. M.; Willis, S. J.; Cook, C. J.; Holmberg, H. C. (PLOS ONE, 2014)
Lower body eccentric exercise is well known to elicit high levels of muscular force with relatively low cardiovascular and metabolic strain. As a result, eccentric exercise has been successfully utilised as an adaptive stressor to improve lower body muscle function in populations ranging from the frail and debilitated, to highly-trained individuals. Here we investigate the metabolic, cardiorespiratory, and energy costs of upper body eccentric exercise in a healthy population. Seven men and seven women performed 4-min efforts of eccentric (ECC) or concentric (CON) arm cycling on a novel arm ergometer at workloads corresponding to 40, 60, and 80% of their peak workload as assessed in an incremental concentric trial. The heart rate, ventilation, cardiac output, respiratory exchange ratio, and blood lactate concentrations were all clearly greater in CON condition at all of the relative workloads (all p,0.003). Effect size calculations demonstrated that the magnitude of the differences in VO2 and work economy between the ECC and CON exercise ranged from very large to extremely large; however, in no case did mechanical efficiency (gMECH) differ between the conditions (all p.0.05). In contrast, delta efficiency (gD), as previously defined by Coyle and colleagues in 1992, demonstrated a sex difference (men.women; p,0.05). Sex differences were also apparent in arteriovenous oxygen difference and heart rate during CON. Here, we reinforce the highforce, low cost attributes of eccentric exercise which can be generalised to the muscles of the upper body. Upper body eccentric exercise is likely to form a useful adjunct in debilitative, rehabilitative, and adaptive clinical exercise programs; however, reports of a shift towards an oxidative phenotype should be taken into consideration by power athletes. We suggest delta efficiency as a sensitive measure of efficiency that allowed the identification of sex differences.